Improved confinement model for reinforced concrete circular bridge columns under static flexural loading - Surepally, Naresh; Prakash, S. Suriya (Journal of Structural Engineering, 2024)
This study presents an improved analytical approach for the analysis of Reinforced Concrete (RC) circular bridge columns by proposing a new confinement model under static loading. Three widely used confinement models are examined and improvements are suggested. It is well known that the stress-strain behaviour of confined concrete is completely different from that of plain concrete. The level of confinement depends on amount of transverse reinforcement, amount of longitudinal reinforcement and spacing of rebars and level of axial load. The influence of these parameters on the section and member level behaviour is analysed and an improved model is proposed for the analysis of RC circular bridge columns under flexure. Predictions of the analytical model are compared with the experimental data of columns tested by the author and others from PEER DATABASE over a range of parameters. The comparisons indicate a very good agreement of the predictions of the proposed model with the test data.